x+25=-3(x-7)

Simple and best practice solution for x+25=-3(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+25=-3(x-7) equation:


Simplifying
x + 25 = -3(x + -7)

Reorder the terms:
25 + x = -3(x + -7)

Reorder the terms:
25 + x = -3(-7 + x)
25 + x = (-7 * -3 + x * -3)
25 + x = (21 + -3x)

Solving
25 + x = 21 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
25 + x + 3x = 21 + -3x + 3x

Combine like terms: x + 3x = 4x
25 + 4x = 21 + -3x + 3x

Combine like terms: -3x + 3x = 0
25 + 4x = 21 + 0
25 + 4x = 21

Add '-25' to each side of the equation.
25 + -25 + 4x = 21 + -25

Combine like terms: 25 + -25 = 0
0 + 4x = 21 + -25
4x = 21 + -25

Combine like terms: 21 + -25 = -4
4x = -4

Divide each side by '4'.
x = -1

Simplifying
x = -1

See similar equations:

| Y-8.1=20 | | 2w^2+15w+27=0 | | 7m-1=34 | | 6(3x+1)=-6x-18 | | 11h-7=-18 | | 2.5=1.3-r | | 2x-4+1= | | 3.3a=5.5b | | (25+x)(10+x)=1000 | | 9a=25b | | 8x-11=13x+15 | | 8.1-y=20 | | 18-x=(11+x)+3 | | 7x-7=2x-1 | | -2m-1=6m+1 | | 30000*12=x | | x^3-10x-21x=0 | | 4-2.5(x+5)=16 | | 5.8=x-72 | | 18-x=12+x | | 314=g+25 | | 6x-5(4x)=-42 | | 12+(-3h)=0 | | 89+x=100 | | 4x+3=2x-6 | | (-2x+3)+(5x-9)=24 | | 4x-5=2x-3 | | (8+3x)+(2-x)=14 | | (2x+10)+(3x-5)=90 | | 6x-14y=5 | | 175+.10m=125+.25m | | v-4=-18 |

Equations solver categories